Local structure and near-infrared emission features of neodymium-based amine functionalized organic/inorganic hybrids - Goncalves, M. C.; Silva, NJO; Bermudez, VDZ; Ferreira, RAS; Carlos, L. D.; Dahmouche, K.; Santilli, Celso Valentim [UNESP]; Ostrovskii, D.; Vilela, ICC; Craievich, A. F. (Amer Chemical Soc, 2005)
Nd3+-based organic/inorganic hybrids have potential application in the field of integrated optics. Attractive sol-gel derived di-urea and di-urethane cross-linked poly (oxyethylene) (POE)/siloxane hybrids (di-ureasils and di-urethanesils, respectively) doped with neodymium triflate (Nd(CF3SO3)(3)) were examined by Fourier transform mid-infrared (FT-IR), Raman (FT-Raman), Si-29 magic-angle spinning (MAS) nuclear magnetic resonance (NMR) and photoluminescence spectroscopies, and small-angle X-ray scattering (SAXS). The goals of this work were to determine which cation coordinating site of the host matrix (ether oxygen atoms or carbonyl oxygen atoms) is active in each of the materials analyzed, its influence on the nanostructure of the samples and its relation with the photoluminescence properties. The main conclusion derived from this study is that the hydrogen-bonded associations formed throughout the materials play a major role in the hybrids nanostructure and photoluminescence properties.